PENEGAKAN HUKUM DISIPLIN PEGAWAI NEGERI SIPIL DALAM MEWUJUDKAN GOOD GOVERNANCE DI TIMOR LESTE - Acacio Frenande Vassalo (Faculty of Law, Universitas Diponegoro, 2014)
Disciplinary regulations of civil servants is made and the applicable rules in a government agency with the purpose of demanding and directing personnel member shall obey him. Labor discipline is important, because the discipline itself as an integral part of the rules that can create working conditions effectively and efficiently. The results showed that the majority of civil servants Distrito Manufahi disobedience againts Law No. 8 of 2004, the cause is political and familiarisme factor that greatly affects the majority of civil servants or civil servants in Distrito Manufahi